An exploration of authorial stance in SSCI-ranked journals versus non-SSCI-ranked journals - Alotaibi, Hmoud S. (Penerbit Universiti Kebangsaan Malaysia, 2019)
Taking an effective authorial stance has been the interest of researchers on academic writing for quite some time. It is agreed upon that the interpersonal aspect of writing is essential in setting up prosody and forcing persuasive argument expected in academic context. This paper is based on a hypothesis that effective and authorial stance is a major principal requirement for publishing in top-ranked journals. Hence, it investigates the linguistic resources employed by authors to realize authorial voices when introducing their research topics and how they relate them with the potential meanings of rhetorical moves to build up persuasive argument. To do this, the study drew on Martin and White's (2005) Appraisal system and Swales' (1990) genre analysis as the two main analytical frameworks for data analysis. The data consisted of sixty research articles (RAs) taken from journals in the linguistics field. Half of the RAs were drawn from SSCI-ranked journals while the other half from other journals that do not have prestigious indexes. The results showed that the percentage of using Monoglossic resources (propositions that contain bare assertions where writer/speaker makes no reference to any alternative viewpoints) is higher in frequency in non-SSCI journals compared to SSCI-ranked journals. Overall, the introduction sections of the two groups of journals have shown a link between the use of evaluative language patterns and the potential meanings of rhetorical moves, which altogether may help project effective authorial stance.